2022
DOI: 10.1002/chem.202200389
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy Groups Enhance [2]Rotaxane Anion Binding Selectivity

Abstract: We report the synthesis of two [2]rotaxanes containing an interlocked three dimensional binding cavity formed from a pyridinium bis(amide) axle component containing two phenol donors, and an isophthalamide based macrocycle. In the competitive solvent mixture 1 : 1 CDCl 3 : CD 3 OD, one of the receptors exhibits a much higher selectivity preference for chloride than an analogous rotaxane without the hydroxy groups. X-ray crystal structures reveal the chloride anion guest encapsulated within the interlocked bind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…[ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] Inspired by nature's oxoanion‐selective protein designs, during the past two decades we have strategically constructed mechanically interlocked host structures (MIMs) for anion recognition. [ 35 , 36 , 37 , 38 , 39 , 40 ] Recently the integration of halogen bonding (XB) donors to decorate acyclic, macrocyclic and MIM receptor binding sites has proven to be a promising alternative to traditionally employed hydrogen bonding (HB) interactions by virtue of the former's often superior anion binding strength, more stringent linear interaction geometries and contrasting selectivity profiles. [ 41 , 42 , 43 , 44 , 45 , 46 ] Surprisingly, the use of interlocked structures for ion‐pair recognition remains remarkably rare, with the handful of reported receptors largely limited to [2]rotaxane topologies,[ 47 , 48 , 49 , 50 , 51 , 52 ] and one example of a [2]catenane topology being used to this end.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] Inspired by nature's oxoanion‐selective protein designs, during the past two decades we have strategically constructed mechanically interlocked host structures (MIMs) for anion recognition. [ 35 , 36 , 37 , 38 , 39 , 40 ] Recently the integration of halogen bonding (XB) donors to decorate acyclic, macrocyclic and MIM receptor binding sites has proven to be a promising alternative to traditionally employed hydrogen bonding (HB) interactions by virtue of the former's often superior anion binding strength, more stringent linear interaction geometries and contrasting selectivity profiles. [ 41 , 42 , 43 , 44 , 45 , 46 ] Surprisingly, the use of interlocked structures for ion‐pair recognition remains remarkably rare, with the handful of reported receptors largely limited to [2]rotaxane topologies,[ 47 , 48 , 49 , 50 , 51 , 52 ] and one example of a [2]catenane topology being used to this end.…”
Section: Introductionmentioning
confidence: 99%
“…While relatively few cationic OÀ H receptors have been reported, [42][43][44][45][46][47][48][49] those that have been prepared have shown relatively high anion affinities in competitive solvents. For example, Yu [44] and Alfonso [45] separately investigated anion recognition using chiral hosts containing cationic imidazolium groups and hydroxy motifs, in both cases demonstrating binding of several anions in very polar organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yu [44] and Alfonso [45] separately investigated anion recognition using chiral hosts containing cationic imidazolium groups and hydroxy motifs, in both cases demonstrating binding of several anions in very polar organic solvents. More recently, we have investigated acyclic [46] and interlocked [48] anion hosts containing amide and hydroxy donors and a pyridinium group and were able to demonstrate selective anion recognition in polar organic solvents containing a small amount of water. We have also demonstrated that the very simple cationic compounds 1 + and 2 + (Figure 1) containing a single charge‐assisted O−H group can bind anions weakly in 9 : 1 CD 3 CN:D 2 O [47] .…”
Section: Introductionmentioning
confidence: 99%
“…[5] Indeed, we and others have demonstrated that MIMs not only raise the bar in terms of anion affinity, but crucially provide a strategy to augment selectivity profiles through a 'mechanical bond effect'. [6][7][8][9][10][11][12][13][14][15] Surprisingly, however, the use of interlocked structures to mediate ion transport remains rare and have thus far been restricted to [2]rotaxane architectures [16][17][18][19] and a molecular knot based ion channel system. [20] Lewis acidic sigma-hole interactions such as halogen bonding (XB) and chalcogen bonding (ChB) are remarkably potent non-covalent means by which anion recognition can be achieved, exhibiting dramatically enhanced affinities relative to traditional strategies including hydrogen bonding (HB), even in highly competitive aqueous media.…”
Section: Introductionmentioning
confidence: 99%